(untitled) (Philology, 2023)
The paper puts forward the idea of applying the scaffolding theory in the teaching of written Chinese according to the needs of development of language teaching environment. The article introduces the source, definition, classification and other basic knowledge of the scaffolding theory, then discusses the application of this theory in actual teaching scenarios according to its classification and characteristics, and finally introduces the application of the scaffolding in teaching Chinese as a foreign language according to the requirements of multimedia teaching environment in the Internet age, and finally discusses the research methods of applying it in the design of support materials for teaching Chinese as a foreign language.